2020
DOI: 10.1080/13625187.2020.1830965
|View full text |Cite
|
Sign up to set email alerts
|

Sexual activity and contraceptive use during social distancing and self-isolation in the COVID-19 pandemic

Abstract: Objectives: The aims of the study were to investigate the effects of social distancing during the COVID-19 pandemic on the use of hormonal contraceptives, their discontinuation and the risk of unplanned pregnancy. Methods: The study enrolled 317 women listed in the database of the Department of General Surgery and Medical-Surgical Specialties, University of Catania, Italy, family planning clinic who were known to be using hormonal contraceptives. The women were contacted by telephone and asked whether they wou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
49
2
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(56 citation statements)
references
References 14 publications
3
49
2
2
Order By: Relevance
“…In a study conducted in Italy in which information was collected from 317 women who used hormonal contraception before confinement authors found that all the women who lived with their partner during the confinement period continued to use their hormonal method, including those who used COC, while those women who did not live with their partner were more likely to abandon the hormonal method they used. 6 In this study, the determining factor for the continuity of use was living with the partner, rather than age. In this case, the mean age of the sample was 26.8 years, while in our study it was 32 years.…”
Section: Discussionmentioning
confidence: 83%
“…In a study conducted in Italy in which information was collected from 317 women who used hormonal contraception before confinement authors found that all the women who lived with their partner during the confinement period continued to use their hormonal method, including those who used COC, while those women who did not live with their partner were more likely to abandon the hormonal method they used. 6 In this study, the determining factor for the continuity of use was living with the partner, rather than age. In this case, the mean age of the sample was 26.8 years, while in our study it was 32 years.…”
Section: Discussionmentioning
confidence: 83%
“…Demand and usage of contraception. Nineteen articles [21,34,75,[98][99][100][101][102][103][104][105][106][107][108][109][110][111][112][113], eleven of which were original research studies [21,34,99,101,103,[106][107][108][109][110]113], considered how demand for contraception changed. There was conflicting evidence on whether the Zika outbreak led to increased demand for contraception [21,34,110].…”
Section: Barriers To Use Of Contraception During Disastersmentioning
confidence: 99%
“…Similarly, while some women reported that they wanted to delay childbearing during the COVID-19 pandemic and considered use of LARC, others did not change their views [75]. However, contraceptive usage during the ongoing COVID-19 pandemic appears to differ amongst married and cohabiting women and non-cohabiting and single women [113]. While married and cohabiting women appear to be more likely to continue their contraception, non-cohabiting and single women were more likely to discontinue contraception [113].…”
Section: Barriers To Use Of Contraception During Disastersmentioning
confidence: 99%
See 2 more Smart Citations